Social Media Literacy For The Millennial Generation In The 4.0 Era: Strengthening Religious Moderation - Rapia Arcanita; Ngadri; Koriatul Sadea; Restu Abdiyantoro (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
In today's world, social media platforms such as Facebook, Instagram, YouTube, and TikTok play an important role in conveying messages, both for amusement and information. However, these technical advancements pose moral issues that can be addressed by religious moderation. Religious moderation promotes balance in religious practice while preventing extreme, revolutionary, and fanatical attitudes. The goal of the study is to determine the strengthening of religious moderation values among IAIN Curup students, to understand social media literacy for the millennial generation of IAIN Curup in the 4.0 era as a means of strengthening religious moderation values, and to identify the influencing factors in the strengthening of religious moderation. Descriptive qualitative research methodology. Data was gathered by observation, interviews, and documentation with PAI, TBI, KPI, and BPI study program students, lecturers, and the Head of PAI, TBI, KPI, and BPI Study Programs at IAIN Curup. The study's findings demonstrate that the millennial generation at IAIN Curup uses a variety of social media platforms such as websites, YouTube, Facebook, WhatsApp, and Instagram to reinforce religious moderation principles in the 4.0 era. Internal and environmental influences influence the strength of religious moderation principles. All parties are more maximum in strengthening the values of religious moderation, both during and after the lecture process.